2016
DOI: 10.1177/0093854816666583
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Demographic Factors, Background Characteristics, and Workplace Perceptions as Predictors of Burnout Among Community Corrections Officers

Abstract: The purpose of this article was to explore the association between demographic and background characteristics, as well as workplace perceptions that may predict burnout among two connected groups of community corrections officers. Using the Maslach Burnout Inventory, we assessed whether burnout differed between probation/parole and residential officers and analyzed whether predictors of burnout varied across these two groups. Our results indicated that while probation/parole officers were more likely to report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 40 publications
1
27
1
Order By: Relevance
“…Unlike the burnout study (Rhineberger-Dunn et al, 2015), we found that gender and educational training were not significantly related to secondary trauma. The existing literature on secondary trauma among PPOs does not address either gender or educational training.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike the burnout study (Rhineberger-Dunn et al, 2015), we found that gender and educational training were not significantly related to secondary trauma. The existing literature on secondary trauma among PPOs does not address either gender or educational training.…”
Section: Discussioncontrasting
confidence: 99%
“…It is noteworthy that the results in this study show both similarities and differences when compared to studies of burnout among PPOs. Prior research on burnout among PPOs found that gender, perceptions of one's health, adequacy of educational training, adequacy of job training, schedule fit, and pay dissatisfaction were significantly related to burnout (Rhineberger-Dunn et al, 2015). The current study is similar in that we found health and job training to be important predictors of secondary trauma.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Then in 2005, the U.S. Department of Justice released a report on the factors influencing stress, and what could be done to mitigate it, among probation and parole officers (Finn & Kuck, 2005). Since that report came out, a few more studies have looked at the impact of job stress on other job-related outcomes (Gayman & Bradley, 2013;Lee, Joo, & Johnson, 2009;Lee, Phelps, & Beto, 2009), and two additional studies were published looking at the factors predicting job stress among community corrections staff (Pitts, 2007;Wells et al, 2006).…”
Section: Job Stressmentioning
confidence: 99%
“…2. Our community corrections staff feel over extended, exhausted and unappreciated and there is evidence that the longer their tenure in the job, the worse it gets (Rhineberger-Dunn et al, 2017). Many have also become suspicious of the value of so-called evidence informed strategies, especially when those strategies are imposed rather than allowed to germinate and grow into acceptance.…”
mentioning
confidence: 99%